New chemistry with anionic NNN pincer ligands - Melen, Rebecca L.; Gade, Lutz H. (The privileged pincer-metal platform, 2016)
The use of tridentate anionic pincer ligands in organometallic chemistry has gained considerable importance, particularly in the field of homogenous catalysis. This chapter focuses on the recent developments of anionic tridentate NNN pincer ligands from their synthesis to coordination chemistry and their applications in forming stable transition metal complexes for applications in catalytic transformations.
Erschienen am 01. Januar 2015
Gesehen am 19.12.2022